Understanding maternal mortality from top–down and bottom–up perspectives: Case of Tigray region, Ethiopia - Hagos Godefay; Peter Byass; John Kinsman; Afework Mulugeta (Journal of Global Health, 2015)
Background: Unacceptably high levels of preventable maternal mortality persist as a problem across sub–Saharan Africa and much of south Asia. Currently, local assessments of the magnitude of maternal mortality are not often made, so the best available information for health planning may come from global estimates and not reflect local circumstances.